FORMS OF OCCURRENCE OF GOLD, SILVER AND MERCURY AND THEIR DISTRIBUTION PATTERNS IN ORES AND ENDOGENOUS HALOES OF GOLD-SILVER DEPOSITS - Kravtsova R.G.; Andrulaytis L.D. (My University, 1989)
One method of increasing the efficiency of the prediction of gold-silver ore occurrences that supplements vertical mineralogical and geochemical zoning is analysis of the forms of occurrence of elements in ores and endogenetic haloes. What one looks for here is systematic distribution and vertical change in the forms of occurrence of gold, silver and mercury. Chemical analysis of the phases proves to be an effective method of studying the forms of occurrence of elements in ores and haloes of the surficial low-sulfide gold-silver association, whose mineragraphic investigation is difficult. An advantage of the phase analysis methods is that they are relatively simple and rapid and can be applied to a wider range of problems. They can be used to study not only mineral forms themselves, but also isomorphic, colloidal and finely divided forms, and they can provide quantitative as well as qualitative information. The zonation of the forms of occurrence of elements of groups of chemical compounds is consistent with the geochemical zonation and supplements and increases the reliability of existing mineralogical and geochemical prospecting techniques. In deposits with a complex polychronic are development, studying the forms of occurrence of the elements is one of a very small number of effective methods of evaluating the extent of the erosional truncation of the various zones.